Evidence-based thoracic epidural nerve block: A systematic review. (2020) - Chekol, Wubie Birlie; Melesse, Debas Yaregal; Denu, Zewuditu Abdissa; Tawuye, Hailu Yimer
Abstract: Background: Thoracic epidural nerve block (TENB) is a technique in which analgesia is produced by injecting local anesthetic agent by itself or combined with additives or alone into the epidural space. This systematic review was designed to improve the quality of pain management and to form a common consensus for TENB based on the current evidences. Methods: PubMed through HINARI was used to get access for current and updated evidences on TENB for cardio-thoracic and major abdominal surgeries. The flow diagram was used to show the filtration methods of suitable literature. Discussion: TENB should be started after checking baseline vital signs and after preparation of emergent phenomenon. The prominent part of C7, T3 scapular spine and the inferior border of T7 are used to localize the intended segment during performing the procedures. Skin infiltration with aseptic technique of 2–3 ml of 2% lidocaine, test dose of 3 ml of lidocaine with 1:200, 000 epinephrine, and loading dose of 3–5 ml of 0.25–0.5% bupivacaine are recommended for TENB. The maintenance dose is 3–5 ml of 0.1–0.25% of bupivacaine. The thoracic epidural catheter will not stay for more than 4 days. Post-procedural care and monitoring should be performed for patients on thoracic epidural catheter. Conclusion: Generally, appropriate preoperative patient evaluation, pre-procedural preparation of the necessary materials, and consideration of the possible options should be mandatory. Anesthetists should be familiar with the landmark techniques, troubleshooting, administration of safe doses of the drug, and post-epidural catheter insertion care. Highlights: Thoracic Epidural Nerve Block should be started after checking baseline vital signs. Thoracic Epidural Nerve Block is indicated for thoracoabdominal procedures. Thoracic epidural catheter will stay for not more than 4 days. Post-procedural cares and monitoring should be given for patients with thoracic epidural catheter.